Evaluation of the blood transfusion strategy in Baghdad Teaching Hospital - AL- Khalissi, Khudhair A.; Abbas, Mohamed A.; Kareem, Zeyad (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Guidelines for blood products transfusion are needed to avoid unnecessary blood transfusion in acute and chronic anaemias to minimize complications.Objective: To evaluate the practice of blood transfusion in Baghdad Teaching Hospital.Patients and methods: One hundred and sixty adults Iraqi patients, who had blood transfusion, were selected randomly from different wards of Baghdad Teaching Hospital including General Medicine (GM), General Surgery (GS), Gynecology/Obstetrics (G/O), forty patients from each ward, from October 2011 to October 2012. Collected data included age, gender, type of ward, indication for transfusion, pre-transfusion packed cell volume (PCV) and hemoglobin (Hb), type (whole blood or red blood cells (RBCs)) and number of units transfused.Results: Pre-transfusion PCV was >30% (Hb >10gm/dl) in 23.1% of the patients, and were highest in G/O (47.5%) and GS (37.5%) wards. Whole blood was given instead of RBCs to 60% of patients (100% in G/O and GS).Single unit blood was given to 22.5% of patients (37.5% in G/O and 35% 1n GS.Conclusion: There is general unawareness of the risks of blood transfusion in Baghdad Teaching Hospital as shown by the use of whole blood instead of RBCs and single unit transfusion, so a more restrictive strategy is needed by following the international guidelines.